Oxygen Therapy - Bonnie Solmes (Canadian Respiratory Journal)
LTOT is prescribed for people with chronic lung disease in whom there is a decrease in the ability of the lungs to supply enough oxygen to the body. The heart is obliged to pump faster to meet the body's oxygen requirements. This may place undue stress on the heart, resulting in palpitations, dizziness and fatigue. A low oxygen level in arterial blood is also harmful to the heart, the brain and the pulmonary blood vessels. Oxygen therapy is used to break this cycle. A person with low blood oxygen will often be able to accomplish more with less fatigue with the help of supplemental oxygen therapy. Shortness of breath is a mechanical problem resulting from the effects of chronic obstructive pulmonary disease. Oxygen therapy may or may not reduce shortness of breath, but it will help the lungs and heart to function with less stress.